Visual Merchandising dan Motivasi Hedonik terhadap Pembelian Impulsif - Tri Seno Anjanarko; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
People's culture that is more consumptive has resulted in high impulsive purchases. With this phenomenon, store managers are expected to be able to take advantage of consumer behavior. Impulsive buying can occur because of the appeal that stores provide as visual merchandising. The store manager will be required to make the store look attractive. In addition, the presence of hedonic motivation is also able to increase impulse buying. This study aims to determine the role of visual merchandising and hedonic motifs on impulsive purchases at a shopping center in Surabaya. This study spread 200 questionnaires with a response rate of 65.5% so that the data processed were 131 questionnaires. The research data will be tested with multiple linear regression with SPSS software. The results of the analysis show that visual merchandising plays a significant role in impulse buying. Impulsive buying is also significantly influenced by hedonic motivation. The two independent variables of the study provide a significant role in impulsive buying together